Pelatihan Pembuatan Media Pembelajaran Berbasis IT (Powtoon) Bagi Guru TK di Kabupaten Pangkep - Amri, Nur Alim; Latief, Fadhilah; Intisari, Intisari; Hajerah, Hajerah; Bachtiar, Muhammad Yusri; Hasmawaty, Hasmawaty (KARYA: Journal of Educational Community Service, 2025)
This community service activity raises the theme of introducing learning videos that have been developed using the powtoon application so that it displays better audio and visuals as teaching materials for children. This application can be used to make videos, create animations using quite complete features, templates, audio, and interesting images so that it is very suitable for use in developing learning media, especially at the Kindergarten age level. This training specifically provides assistance on 1) introduction to application-based learning media, 2) skills training using technology-based learning media, 3) skills training in developing application-based learning media, 4) learning practices using application-based media. The target output of this study is the existence of simple learning media in video format developed using the powtoon application/software with a duration of no more than 10 minutes. The theme used in the video is adjusted to the learning theme in the curriculum in Kindergarten in general so that the output can later be used by each educational unit in the learning process